Rola eksploatacji biopaliw w rozwoju lokalnym na przykładzie wierzby energetycznej - Pingwarska, Renata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The development of renewable energy sources constitutes the strategic goal of the energy policy of the European Union. Due to the accession of Poland to the EU our country is obliged to observe and also to adjust its regulations to the regulations valid and binding in the area of the EU. The determined quantity goals included in the "Accession Treaty" obligate our country to generate the electric energy from the renewable energy sources in the amount of 7.5% of the whole balance of electric energy consumption until 2010. The adaptation of regulations in the scope of power industry and environmental protection opens for the local community a new area of activity which will directly influence the local economy and encourage local business initiatives. The biomass production will allow for the formation of a basis which will facilitate local development. Whether local community benefits from it or not depends on the adopted attitude of the local self-governments which may stimulate the local energy market by serious treatment of energy planning. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 422-432